Personalized medicine in pancreatic cancer: Harnessing the potential of mRNA vaccines - Aariz Hussain; Areeba Fareed (Journal of Genetic Engineering and Biotechnology)
Pancreatic ductal adenocarcinoma (PDAC) is a highly lethal cancer with a five-year survival rate of just 7%. Its late diagnosis and limited treatment options contribute to poor outcomes. Immunotherapy has had little success due to PDAC’s dense and immunosuppressive tumor environment. Emerging mRNA vaccines, such as autogene cevumeran (BNT122), show promise in enhancing treatment. Preliminary trials have reported prolonged survival with minimal side effects. Despite this progress, the complexity of PDAC remains a significant challenge. Continued research is essential to fully realize the potential of mRNA-based therapies in combating this deadly cancer.